Prospective review of cytotoxic snakebite envenomation in a paediatric population. (30th January 2021) - Variawa, Saffiya; Buitendag, Johan; Marais, Ruzaan; Wood, Darryl; Oosthuizen, George
Abstract: Cytotoxic snakebite envenomation is prevalent in Kwazulu-Natal and may be associated with significant physical disability. The aim of this study was to provide an overview of the effects of cytotoxic envenomation in children. The patient population were all patients attending the Emergency Department at Ngwelezana Tertiary Hospital with snakebite from December 2014 to March 2015. All children 13 years or younger presenting with painful progressive swelling (PPS) following snakebite were included in this study. They were further classified according to severity: mild, moderate and severe. Patient demographic and clinical data was collected prospectively. Fifty-one children were included in this study. Nine were classified as mild, 24 as moderate and 18 as severe. The median time of presentation after bite was 6 h in the mild group, 7 h in the moderate group and 12 h in the severe group. There was a positive correlation between increasing severity and INR (p=< .00001) and no correlation between WCC (p = .175) or renal function and severity (p = .963). A total of 11 children (22%) developed an acute kidney injury (AKI). A total of 23/51 patients received antivenom; 25% of patients with moderate cytotoxicity and 94% of patients with severe cytotoxicity. Thirteen percent developed allergic reactions (3/23) and 57% (13/23) anaphylaxis. A total of 15 patients underwent one or more procedures on their affected limbs. There was one recorded mortality during this period, related to severe anaphylaxis following antivenom administration. Access to healthcare for antivenom administration is often delayed and ongoing education within affected areas is advised. Whilst majority of snakebite victims can be adequately managed with basic supportive measures, early identification of severe envenomation is crucial to enable timeous antivenom administration and prevention of further complications such as compartment syndrome and loss of limb. Hypersensitivity reactions are alarmingly common following antivenom administration in children and strict protocols should be followed when administering antivenom. Highlights: Access to healthcare for antivenom administration is often delayed and ongoing education within affected areas is advised. Children appear to have a high risk for severe envenomation and a high rate of anaphylaxis from antivenom. Early antivenom administration may prevent adverse outcomes following severe cytotoxic envenomation. Administration of antivenom should ideally be done in a high care or resuscitation setting under close monitoring.